Optimalisasi Konservasi Energi Bangunan Bertingkat melalui Pilihan Material Kaca sebagai Fasad - Hari Utama; Erni Setyowati (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2022)
Box-shaped buildings covered by glass and minimal shading elements are increasingly common, then causes more large building energy consumption. This research aims to analyze the selection of the most optimal glass material for the Undip Integrated Laboratory Building, so that the Overall Thermal Transfer Value (OTTV) of the building is expected to meet the SNI 6389:2020 standard. The research was conducted with an experimental quantitative approach using a spreadsheet calculator OTTV Microsoft Excel of the Ministry of Public Works and Housing. The simulation is divided into three treatment variations, namely variations in BNFL glass thickness; variations in the color of Panasap's glass; and various types of glass. The results show that glass materials with good thermal properties have low shading coefficient (SC), solar factor (SF), and U-value. In addition, the brighter and thicker the glass material, the better the thermal performance. The Undip Integrated Laboratory Building has a total OTTV that meets SNI 6389:2020 standards. However, if viewed partially, the OTTV of the east facade of the building needs to be retrofitted.